2011
DOI: 10.1371/journal.pone.0019547
|View full text |Cite
|
Sign up to set email alerts
|

Capsular Serotype and Antibiotic Resistance of Streptococcus pneumoniae Isolates in Malaysia

Abstract: Background Streptococcus pneumoniae is a major causative agent of severe infections, including sepsis, pneumonia, meningitis, and otitis media, that has since become a major public health concern. In this study, the serotypes distribution of pneumococcal isolates was investigated to predict the efficacy of the 7-valent pneumococcal conjugate vaccine (PCV7) among the Malaysian populations.Methodology/Principal FindingsA total of 151 clinical isolates were serotyped using multiplex PCR assays. Out of them, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 19 publications
6
25
1
Order By: Relevance
“…This data suggest that almost 56% (144/255 isolates) are resistant to erythromycin and carry the resistant genes. Similar findings [21], which found more than 50% of the pneumococcal isolates from Asia carry the ermB and mefA gene. Based on these findings, it may be suggested that the use of single macrolide for the treatment of pneumococcal diseases may result in failure of antimicrobial therapy.…”
Section: Discussionsupporting
confidence: 83%
“…This data suggest that almost 56% (144/255 isolates) are resistant to erythromycin and carry the resistant genes. Similar findings [21], which found more than 50% of the pneumococcal isolates from Asia carry the ermB and mefA gene. Based on these findings, it may be suggested that the use of single macrolide for the treatment of pneumococcal diseases may result in failure of antimicrobial therapy.…”
Section: Discussionsupporting
confidence: 83%
“…28,[111][112][113][114] A recent study in Malaysia showed that serotype 19F had increased antibiotic resistance and was highly invasive. 88 This study also found that out of 151 clinical isolates, 21.2% were penicillin-resistant S. pneumoniae strains, 29.1% penicillin-intermediate, and 49.7% penicillin-susceptible, 88 whereas another study published in 2011 estimated the penicillin resistance rate to be higher, at 31.78%. 115 Besides, erythromycin resistance rates also appeared to be increasing from 3% (1996-1997) to 36.8% (1998-2001).…”
Section: Antibiotic Resistancementioning
confidence: 91%
“…In Malaysia, serotype 19F predominated the population at the rate of 20.7%, followed by serotype 6B (9.4%), 19A (6.5%), 23F (6.3%), 14 (5.8%), 1 (5.3%), and 6A (3.8%, not differentiated 6B/A in our previous study [115]). These serotypes accounted for 57.9% of the circulating serotypes in Malaysia.…”
Section: Malaysiamentioning
confidence: 44%